Resilient and sustainable supply chain management in the Indian seafood industry: Post-pandemic strategies for global competitiveness. - A, Benzily; Jain, Vipul (Journal of Neonatal Surgery, 2025)
The Indian seafood sector is at the center of the country's economic system, contributing largely to export earnings and rural incomes. However, the COVID-19 pandemic has exposed critical vulnerabilities to its supply chain, including logistical limitations, labor shortages, and disruptions to global trade. This study investigates resilient and sustainable supply chain management practices for strengthening global competitiveness after the pandemic. A mixed-methods research design was used, where primary data were collected from different stakeholders in the sector, that is, exporters, processors, and fishermen, while secondary data were collected from industry and government reports. Arguably, the study found that digitalization, enhancement of cold chain logistics, sustainable fishing, and export market diversification are critical in enhancing resilience. Further, stakeholder collaboration, investment in processing plants fueled by renewable energy, and adherence to international standards of sustainability have become key strategies. The study identifies that long-term competitiveness relies on the integration of sustainability with resilience, thereby ensuring operational competitiveness while meeting environmental and social responsibilities. The study provides significant contributions to policy formulation and strategic planning, providing a blueprint for the success of the Indian seafood sector in an increasingly dynamic global market.